Densidade populacional de perfilhos do capim aruana sob pastejo de bovinos recebendo níveis de suplemento - Souza, Saimon de Souza e (2015)
Tillering is extremely important in the management of a pasture, as corresponding to an efficient route which plants limit and regulate their leaf area index and adapt to those imposed defoliation practices. The objective of this study was to evaluate the population density of aruana grass (Panicum maximum) under grazing cattle receiving supplementation levels. The work was conducted at the Universidade Tecnológica Federal do Paraná, Campus Dois Vizinhos, from December 2013 until March 2014. The experimental area of 2.8 ha was divided into eight paddocks of 0.35 ha. 16 animals Holstein were used. The experimental design was completely randomized with four levels: 0.0; 0.4; 0.8; 1.2% surcharge based on liveweight in aruana grass pasture. Evaluations of tiller density were determined using a square of 0.0625 m2 in the range of 28 days. Two squares were used per experimental unit, which were fixed at representative points of the average condition of the pasture, and accounted for all basal tillers inside the square.